1989
DOI: 10.1104/pp.91.3.1085
|View full text |Cite
|
Sign up to set email alerts
|

Glycolate Metabolism in Low and High CO2-Grown Chlorella pyrenoidosa and Pavlova lutheri as Determined by 18O-Labeling

Abstract: Photorespiration in Chlorella pyrenoidosa Chick. was assayed by measuring '10-labeled intermediates of the glycolate pathway.Glycolate, glycine, serine, and excreted glycolate were isolated and analyzed on a gas chromatograph/mass spectrometer to determine isotopic enrichment. Rates of glycolate synthesis were determined from 180-labeling kinetics of the intermediates, pool sizes, derived rate equations, and nonlinear regression techniques. Glycolate synthesis was higher in high C02-grown cells than in air-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…A major cellular source of glycolate is photorespiration (Spencer & Togasaki 1981); however, it might be expected that this source would be reduced when ambient CO 2 :O 2 ratios are high, and so this does not appear to be consistent with the observed trends in lipophilic toxin synthesis under acidified conditions. However, another study with a freshwater green alga showed that glycolate production rates were 15 to 20 times higher in elevated CO 2 -grown cells relative to air-grown cells (de Veau & Burris 1989).…”
Section: Future Directionsmentioning
confidence: 93%
“…A major cellular source of glycolate is photorespiration (Spencer & Togasaki 1981); however, it might be expected that this source would be reduced when ambient CO 2 :O 2 ratios are high, and so this does not appear to be consistent with the observed trends in lipophilic toxin synthesis under acidified conditions. However, another study with a freshwater green alga showed that glycolate production rates were 15 to 20 times higher in elevated CO 2 -grown cells relative to air-grown cells (de Veau & Burris 1989).…”
Section: Future Directionsmentioning
confidence: 93%
“…[25]). Moreover, the synthesis of glycolate, one of the photorespiratory intermediates, is stimulated by high DO levels and inhibited by high CO, levels both in high CO,-grown and in air-grown cells of Chlorella pyrenoidosa [26].…”
Section: Discussionmentioning
confidence: 99%